The Effect of Hypoxic and Normoxic Culturing Conditions in Different Breast Cancer 3D Model Systems - Svanström, Andreas; Rosendahl, Jennifer; Salerno, Simona; Jonasson, Emma; Håkansson, Joakim; Ståhlberg, Anders; Landberg, Göran (Frontiers in Bioengineering and Biotechnology, 2021)
The field of 3D cell cultures is currently emerging and material development is essential in striving toward mimicking the microenvironment of a native tissue. By using the response of reporter cells to a 3D environment, a comparison between materials and growth conditions can be assessed, allowing optimization of material composition and microenvironment. Here, the breast cancer cell line MCF7 was cultured in normoxic and hypoxic conditions on patient-derived scaffolds and compared at mRNA and protein levels to cells cultured on 3D printed scaffolds, Matrigel and conventional 2D plastics. Cells cultured on patient-derived scaffolds were closely resembling cells cultured on 3D printed scaffolds, contrasting 2D and Matrigel cultured cells, in both normoxic and hypoxic culturing conditions. These data support the use of either a normoxic or hypoxic culturing condition in assays using native tissues to optimize material composition.